Theatre Programs and Playbills Collection - (:unkn) unknown (My University, 2016)
2016-04-05
Keywords: 19th Century Plays; 20th Century Plays; Actors--Belgium; Actors--Canada; Actors--France; Actors--Great Britain; Actors--Ireland; Actors--Italy; Actors--Japan; Actors--Russia; Actors--Scotland; Actors--United States; International Theatre Programs; Plays--Belgium; Plays--Canada; Plays--England; Plays--France; Plays--Ireland; Plays--Italy; Plays--Japan; Plays--Russia; Plays--Scotland; Plays--St Maarten; Plays--United Kingdom; Plays--United States; Shakespearean actors and actresses; Theatre Programs; Women in the Theatre>United States> Twentieth Century